Diurnal physiological and immunological responses to a 10-km run in highly trained athletes in an environmentally controlled condition of 6 °C - Boukelia, B.; Fogarty, M. C.; Davison, R. C. R.; Florida-James, G. D. (European Journal of Applied Physiology, 2017)
Purpose: The Clara cell protein CC16, secreted from Clara cells in the lung, is discussed as a potential biomarker for toxic effects on the airways. An increased concentration of CC16 in serum may be caused by increased permeability of the lungs. To investigate the changes in P-CC16 in response to an intense exercise bout performed at different times of day (9 am and 4 pm) of highly trained individuals. Method: Using a crossover randomized design, 8 runners (mean VO2max 71 ml/kg.min, SD 6) performed a 10-km time trial run, at 9 am and 4 pm, in an environmental chamber set at 6 °C. Lung function tests and blood sampling occurred at baseline, immediately post and 1 h post time trial. Result: Diurnal differences (P < 0.05) were found for blood neutrophil and lymphocyte counts; with higher values at 4 pm. P-CC16 was higher at the pre- and post-trial time point at 9 am compared to 4 pm. Lung function was not different between or within trials. Conclusion: Morning trial in cold condition caused more physiological strain compared to the same trial in the evening. However, this extra stress caused by zeitgebers could be a useful strategy for athletes, coaches, and general population to improve their running performance and protect their health in cold conditions in the long-term plan.